Deformation and safety control limits of shield tunnel under surface loading effects - Rong BIAN; Bing WU; Yongjun SUN; Tianci WENG; Yonglin XIONG (Shuiwen dizhi gongcheng dizhi)
Surface loading is a primary cause of damage to underground shield tunnel segments, leading to issues such as cracking, joint opening, and misalignment. These damages pose significant challenges to the safe operation of shield tunnels. Previous studies often focused on specific loading modes and have not adequately addressed the mechanical interactions between segment joints during analysis. Therefore, this study utilized ABAQUS finite element software to construct a multi-scale refined three-dimensional finite element model containing segments, bolts, and soil layers. The model accounts for the material nonlinearity of tunnel segments and bolts, as well as the complex interaction between tunnel segments and soil. Through simulation analysis of full-scale segment loading model tests, the accuracy and reliability of the adopted tunnel segment model were verified. Using the established three-dimensional refined model, numerical simulation were then conducted to analyze the effects of different loading magnitudes and forms (including central loading, semi-eccentric loading, and eccentric loading) on underground segment structures. The results show that under surface loading, the longitudinal settlement deformation of shield tunnels exhibits discontinuity and non-uniformity. The settlement within the range of surface loading is relatively large, with greater misalignment and opening at the edges of the loading. A comprehensive analysis of the relationship between tunnel structure deformation, opening amount, and misalignment under different loading forms was conducted, and then the relationship between the opening amount of shield tunnel segments and structural deformation and convergence rate was obtained. The proposed formulas can provide valuable insights for engineering applications.